(untitled) (Res Medica, 2014)
I suppose it is a universally applicable law of human behaviour that when anybody starts a new job they become, for a certain period of time, the New Boy. I suppose it is also an invariable rule that the New Boy feels awkward, foolish, clumsy and mawkish (no connection with the firm of solicitors of the same name). The only unique feature about the world of medicine is that the New Boy syndrome is that much more painful and embarrassing, and lasts a little bit longer, the average being between seven and fifteen years. The cause of the New Boy syndrome has been recognised for many years among ornithologists and behavioural animal psychologists, and it is all to do with the pecking order. To put it concisely, the animal that comes lowest in the pecking order, often called the ’runt’ of the litter (particularly by the others), is pecked by everybody and doesn’t get to peck anyone back. As a result, the runt becomes what we biologists call ’beaten up’. If after a long period of this established order, an even more significant animal is introduced to the system, this newcomer becomes the new runt, and the old runt, delighted to have somebody to kick around at last, relieves the many years of pent-up aggression by beating hell out of the new one. This system can be seen in operation among any assembly of gregarious vertebrates — for example, a duck pond, a chicken run, or the American Presidential Elections.